Disease information disclosure among patients with mental illness and their family members in China - Wang, Yi; An, Siyao; Yang, Xun; Zhang, Zhuoqiu; Li, Shuiying; Yao, Jing; Chen, Ying; Deng, Hong (Frontiers in Psychiatry, 2023)
Objective The disclosure of mental illness is a first and crucial step in alleviating stigma and promoting mental recovery. However, at present, there is a lack of research on this subject in the Chinese context. Therefore, we conducted this survey among patients with mental illness and their family members and analyzed the influencing factors. Methods Questionnaires were distributed to qualified patients with mental illness and their family members, who were enrolled from the inpatient departments of two major mental health centers in China. Hierarchical linear regression analysis was used to evaluate the factors affecting the disclosure of disease information by patients with mental illness and their family members. Results A total of 153 patients and 159 family members were included. The percentages of patients and family members who intended to disclose disease information were 34.6 and 18.2%, respectively. Regarding the benefits of being out (BBO), marital status and the number of hospitalizations explained 13.1% of the variance, and stigma explained 4.3% of the variance. Regarding the reasons for staying in (RSI), marital status and family history of mental illness explained 14.4% of the variance, and stigma explained 14.8% of the variance. In the model predicting the influencing factors of family member disclosure, stigma was a predictor of both BBO and RSI, explaining 8.1 and 8.7% of the variance, respectively. Conclusion Both patients and their families were more reluctant than willing to disclose. Marital status, number of hospitalizations and family history of mental illness were all influencing factors of patients’ intentions to disclose disease information. Stigma is closely related to disclosure intention and plays an important role in the disclosure intentions of patients and their families. This suggests that the disclosure of disease information is complex, and many factors need to be considered. Disclosure guidelines should be tailored to individuals.